Pelaksanaan Fungsi Pengawasan Badan Permusyawaratan Desa Serta Hambatannya di Desa Tana Rara Kecamatan Loli Kabupaten Sumba Barat - Yosua Oktoriardo Loda; Saryono Yohanes; David Y Meyners (International Forum of Researchers and Lecturers, 2024)
This study aims to: 1), Know the implementation of the supervisory function of the Village Consultative Body and its obstacles in Tana Rara Village, Loli District, West Sumba Regency), Know about - factors that affect the implementation of the supervisory function of the Village Consultative Body and the obstacles in Tana Rara Village, Loli District, West Sumba Regency. To achieve this goal, researchers use data collection techniques through, observation, interviews, and documentation or literature studies. The data obtained from the results of the study were processed using qualitative analysis to find out about the implementation of the supervisory function of the Village Consultative Body and its obstacles in Tana Rara Village, Loli District, West Sumba Regency and Know about- what factors influence implementation of the supervisory function of the Village Consultative Body and its obstacles in Tana Rara Village, Loli District, West Sumba Regency. The results of this study show that: 1. the implementation of the supervisory function of the Village Consultative Body and its obstacles In Tana Rara Village, Loli District, West Sumba Regency has not been fully carried out optimally because of the existence of people who are pro and con to every decision made, Regarding the implementation of the supervisory function carried out has been carried out properly so as to minimize the occurrence of deviations from the implementation of Village Regulations and APBDes. 2. factors that affect the implementation of BPD's supervisory function are affectedby 2 (two) factors, namely internal factors which include community support/participation in BPD, and good cooperative relations between BPD and Village Government. While the second factor is external factors which include the lack of benefits provided to BPD members, facilities and infrastructure, lack of human resources who fill BPD membership and the existence of communities that are pro and con to every decision made.